Sustaining University-Community Partnerships in Providing Relationship Education: A Longitudinal Qualitative Case Study - J. Mitchell Vaterlaus; Linda Skogrand; Kay Bradford; Brian J. Higginbotham (The University of Alabama, 2022)
Relationship education (RE) has gained much public attention as classes have been implemented through state relationship initiatives. Developing university-community partnerships in implementing RE has been thought to increase access to underserved populations and increase awareness of healthy relationships in a community. Evaluation of these partnerships is just beginning. This three year longitudinal qualitative study represents five Cooperative Extension faculty members' experiences with university-community partnerships in providing RE on a county level. Faculty members described their experiences identifying partners and outcomes from establishing partnerships and forming and sustaining partnerships. Results are discussed in terms of interdisciplinary university-community partnership literature and implications.